Is there a future for Carbon Capture and Storage in Poland ? - Michal Drabik (Graduate Institute Publications, 2014)
The climate is changing, the average temperature on Earth is rising, the EU is concerned and Poland is developing. Despite the fact that the country is trying to make up economically for lost time under Communism, it still has to comply with a demanding EU climate policy. The task is not easy, particularly keeping in mind how heavily coal-dependent the Polish economy is. Consequently, Carbon Capture and Storage (CSS) appears to be a perfect solution. However, the closer the technology is exam...